Cross-border Mergers and Acquisitions in an Emerging Market: Recent Experiences in the Cosmetics Sector in China - Shi, Yuchao (2013)
As the world’s largest emerging market as well as one of the most promising markets, China has attracted increasing attention from foreign companies and has become the largest host destination of foreign direct investment among developing countries. The Chinese cosmetics and beauty industry can be a relatively new but fast-developing sector in recent years. In fact, China has become the fastest growing global beauty and personal care market in Asia and there has been an industry trend of large multinationals buying up domestic Chinese cosmetics brands. The objectives of this paper are then to investigate how foreign firms make the choice of FDI modes of cross-border M&As instead of the greenfield investments in the cosmetics and beauty industry in China and to find out the motives of conducting such M&A activities